ASAS KEADILAN SEBAGAI SALAH SATU LANDASAN HAKIM DALAM MEMUTUSKAN PUTUSAN PERCERAIAN - Abdulah Pakarti, Muhammad Husni; Farid, Diana; Utama, Sofyan Mei; Syuhada, Otong; Hendriana, Hendriana (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2023)
This study aims to analyze the role of the principle of justice as one of the foundations for judges in deciding divorce decisions. In the context of family law, divorce is a complex issue that affects the lives of many individuals. Therefore, it is important for judges to consider various aspects, including the principle of justice, in making fair and just decisions. The research method uses a qualitative approach with the method of analyzing literature and literature studies. Data will be collected from various sources, including books, scientific journals, laws and regulations, court decisions, and other related documents. Data analysis will be carried out by identifying the main themes related to the principle of justice in divorce decisions. The results of the study show that the principle of justice has a very important role in deciding divorce decisions. The principle of justice provides a basis for judges in assessing various factors related to divorce, such as the rights of spouses, children's welfare, distribution of joint assets, and financial obligations. In addition, the Judge must be fair in considering the interests and needs of each partner, as well as the rights of the children involved. In this case, the judge must consider factors such as income, role in marriage, ownership of property, and physical and mental health conditions. In conclusion, the principle of justice plays an important role in deciding on a divorce decision. Judges must consider various factors and principles of justice in ensuring a fair decision for all parties involved. This research makes an important contribution to our understanding of the principle of justice in the context of family law, and provides useful guidance for judges in making fair decisions in divorce. Â Penelitian ini bertujuan untuk menganalisis peran asas keadilan sebagai salah satu landasan bagi hakim dalam memutuskan putusan perceraian. Dalam konteks hukum keluarga, perceraian merupakan masalah kompleks yang mempengaruhi kehidupan banyak individu. Oleh karena itu, penting bagi hakim untuk mempertimbangkan berbagai aspek, termasuk asas keadilan, dalam membuat keputusan yang adil dan berkeadilan. Metode penelitian menggunakan pendekatan kualitatif dengan metode analisis literatur dan studi kepustakaan. Data akan dikumpulkan dari berbagai sumber, termasuk buku, jurnal ilmiah, peraturan perundang-undangan, putusan pengadilan, dan dokumen-dokumen terkait lainnya. Analisis data akan dilakukan dengan mengidentifikasi tema-tema utama yang berkaitan dengan asas keadilan dalam putusan perceraian. Hasil penelitian menunjukkan bahwa asas keadilan memiliki peran yang sangat penting dalam memutuskan putusan perceraian. Asas keadilan memberikan landasan bagi hakim dalam menilai berbagai faktor yang terkait dengan perceraian, seperti hak-hak pasangan, kesejahteraan anak, pembagian harta bersama, dan kewajiban finansial. Selain itu, Hakim harus adil dalam mempertimbangkan kepentingan dan kebutuhan masing-masing pasangan, serta hak-hak anak yang terlibat. Dalam hal ini, hakim harus mempertimbangkan faktor-faktor seperti penghasilan, peran dalam pernikahan, kepemilikan harta, dan kondisi kesehatan fisik dan mental. kesimpulannya, asas keadilan memainkan peran penting dalam memutuskan putusan perceraian. Hakim harus mempertimbangkan berbagai faktor dan prinsip keadilan dalam memastikan keputusan yang adil bagi semua pihak yang terlibat. Penelitian ini memberikan kontribusi penting bagi pemahaman kita tentang asas keadilan dalam konteks hukum keluarga, dan memberikan panduan yang bermanfaat bagi hakim dalam membuat keputusan yang adil dalam perceraian.